Holothurian (Echinodermata) diversity and distribution in the central Cantabrian Sea and the Avilés Canyon System (Bay of Biscay) - Fernández-Rodríguez, Irene; Arias, Andrés; Anadón, Nuria; Acuña, José Luis (Zootaxa, 2019)
Here we report on the holothurian fauna at the Avilés Canyon System (Natura 2000 Site of Community Importance), central Cantabrian Sea, northern Spain. The samples were collected during several cruises covering the shelf, the continental slope and the abyssal depth. We identified 174 specimens, belonging to 35 species of the seven orders of class Holothuroidea. Depth was the main structuring agent. Multivariate analysis allowed the differentiation of four main assemblages which corresponded to abyssal plain, lower continental slope, upper continental slope, and continental shelf. Depth had a significant effect on holothurian species richness (it increased with depth at an approximate rate of 1.7 species 1000 m-1), which is consistent with previously described global patterns.